Sistem Informasi Pengajuan Klaim Asuransi Kendaraan Berbasis Web Menggunakan UML - Anton Sujarwo; Adika May Sari; Rina Lestari; Desri Yani (STMIK Budi Darma, 2020)
The development of technology and information is very helpful in an organization. Organizations in the company, namely PT. Chubb Syariah Indonesia insurance in the Vehicle Claim Filing information system is still using manual systems or has not been computerized, this results in a lack of effective and efficient Vehicle Claim Submission information. So the need for an effective and efficient Vehicle Claim Submission information system with a computerized website-based system, to help expedite the management of Vehicle Claim Submission information. To develop a Vehicle Claim Submission information system that uses the waterfall method. The test results show that the information system is able to make the process of filing a Vehicle Claim online can be effective and efficient